283 Injury prevention in professional football: perceptions and strategies of 72 Brazilian football clubs. (3rd March 2020) - de Souza Guerino Macedo, Christiane; Freitas, Fernando Cassiolato; Fujisawa, Dirce Shizuko
Abstract : Background: The scientific literature presents the prevention profile of national teams and clubs from various parts of the world; however, the real situation of Brazilian football has only been described by a single study with teams from the top division (A), which present higher technical level and financial capacity, which does not characterize the reality of football in the country. Objective: To determine the prevention practices and perceptions of professionals from the different series of the Brazilian soccer championship. Design: Qualitative and quantitative study. Setting : Online interviews. Participants : Seventy-two Brazilian football clubs. Interventions : They responded online questions on prevention, perception on injury risk factors, evaluation methods, and injury prevention training exercises. Main Outcome Measures : Development of preventive program, professional responsible for the preventive program, injury risk factors, athlete assessment methods and injury prevention activities. Results : Injury prevention programs were being developed in 64 clubs (89%), 93.8% of clubs in series A and B, 76.9% in C and 88.9% in series D. In 79.7% clubs, the physiotherapist is the most active professional in preventing injuries. Among the predisposing factors of injury were identify biomechanical changes, physical conditioning, muscle imbalance, previous injuries, pitch quality, training load and number of matches per season. The athletes' evaluation involved validated functional tests, isokinetic dynamometry, and serum creatine kinase. Preventive activities included proprioceptive exercises, core training, eccentric, plyometric, and stretching exercises. In this study, 48.4% of preventive measures used by the clubs were based on scientific evidence, 48.4% were partially based, and 3.1% were measures established by the clubs. Conclusions : Brazilian clubs from different series have developed preventive measures based on scientific evidence and the physiotherapist is the most active professional. There was agreement between injury risk factors, evaluation methods, and preventive training.